2021
DOI: 10.1017/s002221512100044x
|View full text |Cite
|
Sign up to set email alerts
|

Using a 4K three-dimensional exoscope system (Vitom 3D) for mastoid surgery during the coronavirus disease 2019 pandemic

Abstract: Objective Microscopic surgery is currently considered the ‘gold standard’ for middle-ear, mastoid and lateral skull base surgery. The coronavirus disease 2019 pandemic has made microscopic surgery more challenging to perform. This work aimed to demonstrate the feasibility of the Vitom 3D system, which integrates a high-definition (4K) view and three-dimensional technology for ear surgery, within the context of the pandemic. Method Combined approach tympanoplasty and ossiculoplasty were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…To overcome the obstacle of personal contamination through patient care, several methods have been studied/suggested (Cottrell et al, 2020;Ally et al, 2021;Chari et al, 2021): personal protective equipment (PPE) for clinics and the ORs, a shift to telehealth communication, environmental protection (microscope draping, tents), modification of surgical settings and alteration of surgical techniques (actively preferring endoscopic approaches, use of exoscopes, use of enhanced smoke/suction devices, povidone-iodine irrigation of mastoid). SARS-CoV-2 testing is pre-operatively advised, and if the test is negative, additional precautions may not be necessary.…”
Section: Changes In Conceptmentioning
confidence: 99%
“…To overcome the obstacle of personal contamination through patient care, several methods have been studied/suggested (Cottrell et al, 2020;Ally et al, 2021;Chari et al, 2021): personal protective equipment (PPE) for clinics and the ORs, a shift to telehealth communication, environmental protection (microscope draping, tents), modification of surgical settings and alteration of surgical techniques (actively preferring endoscopic approaches, use of exoscopes, use of enhanced smoke/suction devices, povidone-iodine irrigation of mastoid). SARS-CoV-2 testing is pre-operatively advised, and if the test is negative, additional precautions may not be necessary.…”
Section: Changes In Conceptmentioning
confidence: 99%
“…As a result, 17 per cent of surgeons in this study did not feel that the image quality or the magnification were adequate for performing the fine middle-ear procedures requested of them, such as manipulation of the ossicular chain. Whilst Ally et al 6 did not find this to be a problem during their combined approach tympanoplasty case study, they did experience glare when looking down the ear canal with a speculum associated with the brightness of the Vitom 3D camera system. Our work found that the glare could be minimised in such cases by reducing the brightness to the desired level via the Vitom 3D system's control console.…”
Section: Discussionmentioning
confidence: 96%
“…This study, with a level of evidence of 4, assessed the feasibility of performing otological surgery using the Vitom 3D exoscope, instead of the traditional operating microscope, whilst donned in full PPE. The literature has demonstrated the safe use of 3D exoscope systems in a range of ENT operations, including lateral skull base work and mastoid surgery, through a series of published case reports 6 , 14 , 15 and retrospective case–control series. 8 , 10 , 12 Our qualitative study was designed to complement the existing body of published work on exoscope systems, by assessing the experience of ENT surgeons at different stages of their career.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations